Evaluasi Desain Antarmuka Aplikasi Mobile SiGap menggunakan Metode Heuristic Evaluation (Studi Kasus pada BPBD Kabupaten Sidoarjo) - Yunita Titisari; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
SiGap application is an official mobile application owned by the Sidoarjo Regency Regional Disaster Management Agency (BPBD). This application is used to facilitate the public in knowing information about disasters that occur in Sidoarjo. However, there were several complaints in application. To explore the problems in the SiGap application, a usability evaluation is needed. The usability evaluation method used in this study is the Heuristic Evaluation method involving 3 usability expert evaluators. In addition, to get deeper data related to the impressions, expectations and goals of a user when accessing the application, a Persona was created to represent the SiGap application users. Evaluation is carried out in 2 stages. The first stage aims to find out application problem. The second stage aims to find problems in the application after an interface design improvement is built based on the evaluation of phase 1 and Persona. Phase 1 evaluation resulted in a total of 21 problem findings, with an average severity rating that can be classified into 3 of 4 categories namely minor, major, and catastrophic. While in stage 2 evaluation, 3 problems were found.